THE IMPACT OF ONLINE GAMING ADDICTION ON MENTAL HEALTH AMONG IIUM STUDENTS - Nur Shazreen Zul Kamal; Saodah Wok (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
This study was designed to examine the impact of online gaming addiction on mental health among International Islamic University Malaysia (IIUM) students. The objectives of this study are to determine: (a) the exposure to online gaming, (b) the levels of online gaming addiction and mental health, and (c) the relationship between online gaming addiction and mental health, particularly depression, anxiety, and loneliness. This study employed a quantitative research design with the network sampling procedure applied as the sampling technique for data selection and an online survey questionnaire as the research instrument. A total of 210 respondents participated in this study, comprising both undergraduate and postgraduate students. The findings show that the most popular type of online game is PlayerUnknown’s Battlegrounds (PUBG), followed by Mobile Legend (ML), Call of Duty (CoD), Defense of the Ancients (DotA), and Free Fire. The levels of online gaming addiction and mental health among IIUM students were found to be significantly low. The relationships between online gaming addiction and mental health components, namely depression, anxiety, and loneliness, were found to be significant and positive. Based on the social cognitive theory tested, all the developed hypotheses were accepted. This study suggests that future research should examine the impact of online gaming addiction on academic performance and physical health. Besides, future research can investigate other theories such as agenda-setting theory, cultivation theory, dependency theory, and media effect theory.